Analytical Correlations for Modeling the Laminar Flame Speed of Natural Gas Surrogate Mixtures. (September 2017) - Amirante, R.; Distaso, E.; Tamburrano, P.; Reitz, R.D.
Abstract: Natural gas is increasingly used as an alternative to petroleum fuels in internal combustion engines and industrial power plants because of its smaller environmental effects, as well as for economic reasons. Many applications, such as the spark-ignition engine simulations and the design of burners, require an accurate calculation of its laminar flame speed. Encouraging progress has been made in developing detailed chemical kinetic models for its prediction, but such models are still extremely complex and require significant computational effort. The laminar flame speed is an intrinsic property that is a function of the unburnt mixture composition, temperature, and pressure, therefore it is possible to develop analytical correlations based on experimental measurements, without losing accuracy, and that are more easily implemented in CFD codes than tabulated data. The purpose of this study is to provide a simple, but accurate expression for modeling the laminar flame speed of natural gas as a function of its composition and over a wide range of operating conditions. In particular, a correlation valid for a natural gas ternary surrogate mixture of methane, ethane and propane is proposed. To achieve this aim, correlations for pure methane, as well as for binary methane/ethane and methane/propane mixtures were derived and combined to obtain a formulation suitable for different compositions of natural gas. It must be highlighted that some empirical correlations are already available in the literature, but they are usually based on a limited set of experimental measurements, thus they can fail outside the range in which they have been validated against experiments. In this study, measurements of laminar flame speeds obtained by several research teams are collected, compared, and critically analysed with the aim to develop more accurate empirical correlations. A comparison with available correlations in the literature shows the improvement in accuracy obtainable with the approach proposed in the present work.